MOJBB 2018
DOI: 10.15406/mojbb.2018.05.00089
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin bioavailability issues and its effect on birth defects

Abstract: The yellow pigment of turmeric (Curcuma longa) i.e. Curcumin (diferuloylmethane has been associated with a number of properties such as antioxidant, anti-inflammatory, neurotrophic activity, antibacterial, antiviral, and anticancer etc. Oxidative stress is believed to be one of a major contributing factor for teratogenesis (congenital birth defects). However, enhanced oxidative stress may cause irreversible embryonic and foetal damage. However, Curcumin attracted attention due to its promising actions but limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…They reported a 7.5-fold higher cell death in curcumin treated blastocysts relative to the control through the generation of ROS and Mitochondria-Dependent apoptotic signaling pathway. On the other hand, recent review on the bioavailability of curcumin and its effects on birth defects was reported by [ 51 ]. Their report described the role of curcumin as a scavenger of ROS, which was implicated by [ 50 ] as the cause of blastocyst death in mouse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported a 7.5-fold higher cell death in curcumin treated blastocysts relative to the control through the generation of ROS and Mitochondria-Dependent apoptotic signaling pathway. On the other hand, recent review on the bioavailability of curcumin and its effects on birth defects was reported by [ 51 ]. Their report described the role of curcumin as a scavenger of ROS, which was implicated by [ 50 ] as the cause of blastocyst death in mouse.…”
Section: Discussionmentioning
confidence: 99%
“…Their report described the role of curcumin as a scavenger of ROS, which was implicated by [ 50 ] as the cause of blastocyst death in mouse. The findings of [ 51 ] show that curcumin can help ameliorate the toxic effects of certain drugs with teratogenic effects prescribe during pregnancy due to their ability to scavenge ROS.…”
Section: Discussionmentioning
confidence: 99%
“…They reported a 7.5-fold higher cell death in curcumin treated blastocysts relative to the control through the generation of ROS and Mitochondria-Dependent apoptotic signaling pathway. On the other hand, recent review on the bioavailability of curcumin and its effects on birth defects was reported by [52]. Their report described the role of curcumin as a scavenger of ROS, which was implicated by [51] as the cause of blastocyst death in mouse.…”
Section: Figure 5: Effects Of Curcuma Longa Extract On Zebrafish Larvmentioning
confidence: 99%
“…Their report described the role of curcumin as a scavenger of ROS, which was implicated by [51] as the cause of blastocyst death in mouse. The findings of [52] shows that curcumin can help to ameliorate the toxic effects of certain drugs with teratogenic effects prescribe during pregnancy due to their ability to scavenge ROS.…”
Section: Figure 5: Effects Of Curcuma Longa Extract On Zebrafish Larvmentioning
confidence: 99%